A Lesson in Boosterism: The Contest for the Alberta Provincial Capital, 1904-1906 - Kilpatrick, Alexander (Urban History Review / Revue d'histoire urbaine, 1980)
Although 1905 marked a major transition in the political life of the old Northwest Territories, attention in Alberta's urban centres was focused not upon the larger questions raised by the granting of provincial status to the area, but rather upon the issue of which of the several competing communities would capture the title of provincial capital. Ambitious boosters in Red Deer, Calgary, Edmonton, Medicine Hat and a host of smaller settlements (such as Banff) coveted capital status for their particular city, town or even village as a symbol of its swelling importance and as an aid to further promotion. Many elements were called into play during the bitter capital campaign that followed the 1904 federal election including the geographical location, the future prospects and the business activities of the various aspirants. None of these factors proved to be critical in the final decision. The victor, Edmonton, emerged triumphant due in almost equal part to the persistent and aggressive actions of its boosters and to the inadequacy or failure of the urban promoters in rival centres. As boosters in Red Deer, Banff, Medicine Hat and Calgary discovered, success in the capital quest was dependent on much more than desire. By utilizing their advocates in both the federal and provincial political arenas and by thrusting their city into the public eye, Edmonton's community boosters gave their competitors an instructional session they would not soon forget.